Las falsas historias contadas en el Silves de la Selva - Giada Blasut (Atalaya)
This paper aims to analyse a peculiar narrative structure of the Spanish chivalric romance, Silves de la Selva, written by Pedro de Luján. In particular, the paper studies the fictitious «historias contadas»: the narrative analepses that do not correspond to the truth, but they were invented to determine the knight’s departure from the court and his consequent captivity by treachery.